2004
DOI: 10.1016/s0014-5793(04)00315-1
|View full text |Cite
|
Sign up to set email alerts
|

The AE2 anion exchanger is necessary for the structural integrity of the Golgi apparatus in mammalian cells

Abstract: The structural integrity of the Golgi apparatus is known to be dependent on multiple factors, including the organizational status of microtubules, actin and the ankyrin/spectrinbased Golgi membrane skeleton, as well as vesicular tra⁄cking and pH homeostasis. In this respect, our recently identi¢ed Golgi-associated anion exchanger, AE2, may also be of importance, since it potentially acts as a Golgi pH regulator and as a novel membrane anchor for the spectrin-based Golgi membrane skeleton. Here, we show that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…However, in contrast to the well-characterized erythrocyte membrane skeleton, even the identities of the components of this surmised network in the Golgi-associated membrane have been elusive. Specific isoforms of spectrin and ankyrin have been recognized in the Golgi, and a recent report has suggested that the AE2 anion exchanger, a member of the red blood cell band 3 (AE1) family, is necessary for the structural integrity of the Golgi complex (Holappa et al, 2004). In the present study, we have identified a previously unknown protein 4.1 variant, 4.1B 200 , as a Golgispecific component.…”
Section: Discussionmentioning
confidence: 58%
“…However, in contrast to the well-characterized erythrocyte membrane skeleton, even the identities of the components of this surmised network in the Golgi-associated membrane have been elusive. Specific isoforms of spectrin and ankyrin have been recognized in the Golgi, and a recent report has suggested that the AE2 anion exchanger, a member of the red blood cell band 3 (AE1) family, is necessary for the structural integrity of the Golgi complex (Holappa et al, 2004). In the present study, we have identified a previously unknown protein 4.1 variant, 4.1B 200 , as a Golgispecific component.…”
Section: Discussionmentioning
confidence: 58%
“…The structural role of the AE2 protein in the Golgi complex would be linked to its function (the reversible electroneutral exchange of Cl À for HCO 3 À ), thus contributing to the regulation of intracellular pH, organelle volume, and chloride concentration. Strikingly, in AE2-depleted cells, Golgi stacks display numerous fenestrations and swollen cisternae [Holappa et al, 2004]. On the other hand, it has also been reported that actin-binding activity is a requirement for transport of (V)H þ -ATPase to and from the plasma membrane [Vitavska et al, 2003;Chen et al, 2004b] and therefore, it is reasonable to assume a role for microfilaments and actin dynamics in the delivery and/or activation of (V)H þ -ATPase in endomembrane systems, including the Golgi complex.…”
Section: Discussionmentioning
confidence: 99%
“…/H ? exchanger family has been reported to contribute to Golgi pH as has the anion exchanger AE2 (Holappa et al 2004). An anion transporter called GPHR (Golgi pH regulator) was recently shown to be essential for maintaining cisternal pH, and the absence of GPHR leads to reduced membrane traffic and morphological disruption of the Golgi complex (Maeda et al 2008).…”
Section: Golgi Luminal Microenvironmentmentioning
confidence: 99%